The Potential Effect Of Sweet Potato (Ipomoea batatas L.) Extract On Total Cholesterol And Low-Density Lipoprotein (LDL) In Hypercholesterol-Model Wistar Rat (Rattus norvegicus) - Meddy Setiawan; Dzikrulloh Abdi; S Khanza Zatalini; Kevin Muliawan Soetanto (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2022)
Introduction: CHD has high development among 86% in the world with the prevalence in urban (0.6%) than rural (0.4 %) areas. Atherosclerosis is an inflammatory response in blood vessels due to hypercholesterolemia and oxidized LDL. LDL and total cholesterol levels can be reduced by anthocyanins compounds, which are contained in purple sweet potato (Ipomoea batatas L.) This study aimed to determine the effectiveness of purple sweet potato extract in reducing total cholesterol and LDL. Methods: This study was a post-test-only control group experimental design. Twenty-five Wistar rats were divided into five groups: normal control, negative control, and three treatment groups fed by purple sweet potato extract doses of 66.67, 133.33, and 266.67 mg/kg BW/day. Results: Based on the statistical analysis there were significant differences between the treatment group and control groups. The highest dose of purple sweet potato extract (266.67 mg/kg BW/day) has an optimal effect in decreasing total cholesterol and LDL levels. Conclusion: Purple sweet potato extract (266.67 mg/kg BW/day) can reduce total cholesterol and LDL levels of Wistar Rats.